Pengaruh Inflasi dan Kurs Terhadap Dana Pihak Ketiga (DPK) Bank Syariah Bukopin - Zulfa Eliza; Iskandar; Sarah (Ali Institute of Research and Publication, 2023)
This study aims to analyze the effect of inflation and exchange rates on the Bukopin Syariah Bank Funds. The source of data in this study is the financial statements of Bank Syariah Bukopin,the exchange rate and inflation data of Bank Indonesia in 2013-1018. The data was obtained from literature study, documentation and archive data trough the Bukopin Bank Islamic financial report websitevin the from Third Party Funds, and Bank Indonesian publication data in the from of exchange rates and interest rates and Central Statistics Agency data in the from of inflation. The type of reseach is quantitative research. The results of this study indicate that the inflation variable has a negatife and not significant effect on Bank syariah bukopin’s third party funds. The exchange rates variable has a negatife and not significant effect on Bank Syariah Bukopin’s third party funds.